External preference mapping: A guide for a consumer‐driven approach to apple breeding. Issue 1 (5th October 2018) - Bowen, Amy J.; Blake, Amy; Tureček, Jessica; Amyotte, Beatrice
Abstract: This research enabled the creation of a predictive tool to determine consumer preference based on sensory characteristics and to understanding consumer liking for a large and genetically‐diverse apple population. Over two consecutive years, 71 and 83 apples were profiled using descriptive analysis for aroma, taste, and texture attributes. Sensory maps were created, which clustered apples into four groups with common profiles: aromatic‐sweet, acidic, balanced, and mealy. Acceptance data from 219 consumers was collected on a representative subset of 19 apples and related to the sensory properties through external preference mapping. Two consumers groups were identified both preferring juicy, crisp apple but differing in preference for fresh red apple aroma and sweetness (Group 1, 89%) versus more acidic apples with fresh green apple aroma (Group 2, 11%). For both groups, mealy texture was a strong detractor of liking. Preferred sensory characteristics did not differ based on consumer age, gender, or ethnic heritage. Practical applications: Understanding consumer preference for fresh apples is key to developing and selecting novel cultivars that will achieve marketplace success. Results are discussed with relevance to a consumer‐driven approach to apple breeding and evaluation of new varieties for commercialization to meet the needs of an evolving apple market.